2010
DOI: 10.3747/pdi.2009.00100
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Inflammation after Twenty-Week Exposure to Dialysis Solution: Effect of Solution versus Catheter–Foreign Body Reaction

Abstract: An indwelling catheter amplifies peritoneal inflammation from dialysis solutions through a foreign body reaction. Our data also suggest that additives to existing solutions may have limited the effect on inflammatory response to non-biocompatible solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…Interestingly, these animals had more striking histopathologic alterations of the peritoneum than animals treated with a 4% glucose solution through a catheter for 20 weeks. Animals that did not have a catheter implanted but received daily IP injections of the dialysis solution, on the other hand, exhibited relatively less alterations in the peritoneum (13). In the current study, we observed significantly increased levels of fibrosis, manifested by increased peritoneal thickness, and increased vascular density after 8-week exposure to the peritoneal catheter.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Interestingly, these animals had more striking histopathologic alterations of the peritoneum than animals treated with a 4% glucose solution through a catheter for 20 weeks. Animals that did not have a catheter implanted but received daily IP injections of the dialysis solution, on the other hand, exhibited relatively less alterations in the peritoneum (13). In the current study, we observed significantly increased levels of fibrosis, manifested by increased peritoneal thickness, and increased vascular density after 8-week exposure to the peritoneal catheter.…”
Section: Discussionsupporting
confidence: 59%
“…Furthermore, animals with silicone catheters tunnelled into the peritoneal cavity that were not exposed to dialysis solutions exhibited changes in the peritoneum at 4 weeks after catheter implantation (13). Interestingly, these animals had more striking histopathologic alterations of the peritoneum than animals treated with a 4% glucose solution through a catheter for 20 weeks.…”
Section: Discussionmentioning
confidence: 91%
“…Some patients, especially those with diabetes mellitus, seem to present an altered production of fibroblast or vascular growth factors (8,9). Other cases might be related to complications or to the catheter itself, for example leakage, bleeding, intestinal lesion, bacterial contamination, Dacron fibers or chemical contaminants (10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…Daily injection of PDF (100 ml/kg, once or twice daily) was performed for up to 8 or 12 weeks to obtain morphological changes in the rat peritoneum [71][72][73]. Implantation of a silicon catheter into the rat abdomen was reported to amplify peritoneal inflammation from PDF through a foreign body reaction [74]. However, the peritoneum of rats that received only a puncture without infusion of any solution showed no functional or pathological changes [73,75].…”
Section: Zymosan-induced Fungal Peritonitis Modelmentioning
confidence: 99%
“…Other models of non-infectious peritoneal injury associated with inflammation and fibrosis Administration of PDF into the abdominal cavity of rats and mice by repeated intraperitoneal injection or implanting a catheter is a method used to study the pathophysiological changes of the peritoneum associated with PD [69][70][71][72][73][74][75][76][77][78][79][80][81][82][83], but a non-peritonitis model. Daily intraperitoneal injection of 4.25% glucose dialysate into the rat abdominal cavity for 1 week induced an increased peritoneal membrane transport rate and the absence of the peritoneal surface layer, as observed by electron microscopy [69,70].…”
Section: Zymosan-induced Fungal Peritonitis Modelmentioning
confidence: 99%